Strategi Penurunan Kecemasan Perawat di Ruang Perawatan Covid-19 - Zatihulwani, Eliza Zihni; Faizah, Rohmatul (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: The psychological response experienced by nurses to infectious disease pandemics is increasing because it is caused by feelings of anxiety about the health of themselves and their families. Nurses in the Covid-19 isolation room stated that family support was very important to reduce nurses' anxiety in carrying out their duties. The purpose of the study was to determine the relationship between family support and nurses' anxiety levels in dealing with Covid-19 patients.Methods: The research design used was non-experimental with a correlational research design and a cross-sectional approach. Total population is 45 nurses. The sampling technique was purposive sampling, the sample used was 32 nurses. Collecting data using a questionnaire that has been tested for validity and reliability by researchers. Analysis of the data used is rank spearmen.Results: The results showed that most of the nurses' family support was moderate, as many as 20 respondents (62.5%) and most of the nurses' anxiety levels were moderate, namely 17 respondents (53.1%). The results of the Spearman rank test show that there is a relationship between family support and the level of anxiety of nurses in dealing with Covid-19 patients, the significance value of P: 0.00 < : 0.05.Conclusion: Health institutions should pay more attention and immediately implement policies that support efforts to maintain and restore the mental health of nurses. Steps that can be considered include: forming groups that can support efforts to resolve anxiety, providing counseling services, and coping training.